The EVALUASI DESAIN DAN KINERJA ALAT VACUUM TEST SEBAGAI METODE NON DESTRUCTIVE TESTING (NDT) PADA SAMBUNGAN LAS - ALESSANDRO BRILLIANT; Ilham Arifin Pahlawan; Aufa Ulin Nuha (ENIGMA: Engineering in Green Machinery, 2025)
This study  focuses on the assembly and testing process of a Vacuum Test device as one of the Non-Destructive Testing (NDT) methods for detecting leakage in welded joints. The activities were conducted at PT. Kintomo Engineering Group, Gresik, with the objective of understanding the working principles, assembly procedures, and effectiveness of the Vacuum Test device in industrial applications. The methods applied included direct observation, participation in technical activities, and simulation analysis using Autodesk Inventor software. The test results indicate that the Vacuum Test device is capable of achieving vacuum pressures of 50–100 mbar and performs effectively in detecting defects such as porosity and micro-cracks in welded joints. Simulation results show a maximum stress of 0.613 MPa with a safety factor of 15, indicating that the device is structurally safe for repeated use. Based on these findings, the Vacuum Test method is proven to be an effective visual inspection tool for detecting leakage without causing damage to the material structure.